A retrospective study of pediatric thyroid eye disease: the Asian experience. (2nd January 2022) - Sim, Bryan; Chng, Chiaw Ling; Audrey, Chia; Seah, Lay Leng
ABSTRACT: Aim: To study the clinical presentation, disease characteristics, and management approach for children with thyroid eye disease (TED) over a 10 year period in a multidisciplinary Paediatric Thyroid Eye Disease Clinic at a tertiary care referral center. Methods: Retrospective case series of patients with TED at Kandang Kerbau Women's and Children's Hospital (KKWCH) Singapore between August 2006 to June 2015. The diagnosis of TED was clinical based on the Bartley criteria. Ophthalmic examination findings, systemic thyroid function and ophthalmological intervention were recorded. Results: Nineteen subjects with pediatric TED were studied. The median age at diagnosis was 12.5 years (range 6–17). The onset of TED was at the same time as their thyroid disease in half of these patients (52.6%) of which all were hyperthyroid except one. The most common signs at TED diagnosis were proptosis (84.2%), lid retraction (63.2%), acquired epiblepharon (63.2%). All patients were inactive and none had evidence of compressive optic neuropathy. TED remained stable in all patients except for one who developed worsening proptosis with exposure keratopathy. No patients were prescribed steroids (oral or intravenous) or had orbital decompression surgery. The most debilitating morbidity was acquired epiblepharon of which out of 12 patients, one had everting sutures and three were offered surgical correction. Conclusions: Paediatric TED subjects exhibit milder clinical manifestations compared to adults. Acquired epiblepharon causes most significant visual morbidity by compromising the corneal surface. Being cognizant of the subtleties of pediatric TED will permit the discerning clinician to effectively manage such cases accordingly.